问题标题:
y=arctanxarccotx求导
问题描述:
y=arctanxarccotx求导
陈一林回答:
y'=(1/(1+x^2))arccotx-(1/(1+x^2))arctanx
=(1/(1+x^2))*[arccotx-arctanx]
=(-1/(1+x^2))*arctan[(xy-1)/(y+x)]
黄德根回答:
最后一步arctan「(xy-1)/(yx)怎么来的
陈一林回答:
tan(A-B)=(tanA-tanB)/(1+tanAtanB)A=arctanx,B=arccotx=arctan(1/x)tan(arctanx-arccotx)=(tanA-tanB)/(1+tanAtanB)=(x-1/x)/(1+x/x)=(1/2)(x-1/x)=[(x^2-1)/(2x)]arctanx-arccotx=arctan[(x^2-1)/(2x)][arccotx-arctanx]=-arctan[(x^2-1)/(2x)]y'=(1/(1+x^2))*[arccotx-arctanx]=(-1/(1+x^2))*arctan[(x^2-1)/(x+x)]=(-1/(1+x^2))*arctan[(x^2-1)/(2x)]
点击显示
数学推荐
热门数学推荐